ARM (ACCEPT, REJECT AND MODIFY) AS AN ALTERNATIVE TECHNIQUE IN TEACHING SPEAKING - Susanto, Dias Andris (ENCOUNTER, 2012)
This research reports on the result of a study about ARM (accept, reject and modify) as an alternative technique in teaching speaking at the English department of IKIP PGRI Semarang. In depth research with 2 classes (experimental and control) at the department were conducted to improve the studentsâ achievement in speaking. The objective of the research is to find out the improvement of studentsâ speaking achievement after taught through ARM (Accept, Reject and Modify) technique. The researcher applied experimental research which contained 2 activities to collect the data. They were pre-test and post-test. In analyze the data; it was found that there was positive effect of teaching speaking through ARM. For the purpose of the research, the researcher used the significant level at 0, 05 (5%) and the calculation showed that the value of t table = 2, 002 and t test = 9, 56. It meant t test was higher than t table with degree of freedom (df) = 58 was 2, 002. The result of the studentsâ progress during the teaching and learning process by using ARM technique was good. Based on the result above, it can be concluded that there is the improvement of studentsâ achievement in speaking through ARM by the second year of English department of IKIP PGRI Semarang and ARM is a good technique for teaching speaking and the students were able to apply this technique well. In line with the result, it is conducted that the use of ARM technique is very beneficial and good feedback to the students in improving studentsâ skill in speaking. It is recommended that the technique is applied in class regularly and continually because the students were interested in using the technique. By any creative activities arranged, it can be expected that there will be interactive communication between teacher and students in teaching learning process and the students should more practice of speaking in daily life.